Pengembangan lembar kerja peserta didik dengan model problem-based learning pada materi koordinat kartesius - Nisa, Khairun; Sakur; Yuanita, Putri (Jurnal Pendidik Indonesia, 2025)
This study is a development research aimed at producing a valid and practical Student Worksheet for the Cartesian coordinate material. The development model used in this study is the 4-D model (define, design, develop, and disseminate). The product developed is a learning worksheet based on the Problem Based Learning (PBL) model for eighth-grade students of junior high schools (SMP/MTs) on the Cartesian coordinate topic. This worksheet has undergone a validation process by three validators, a one-to-one trial with three students to assess readability, and a small group trial with 15 students, all of which indicated that the worksheet met the criteria for validity and practicality. The validation results showed an average percentage of 91.61%, categorized as very valid. Furthermore, the practicality results obtained from the small group trial showed an average percentage of 89%, categorized as very practical. Thus, it can be concluded that the development of the worksheet using the Problem Based Learning model for the Cartesian coordinate topic in eighth-grade SMP/MTs has met the criteria for being both valid and practical.